COASTAL RECLAMATION AND ITS IMPLICATION TOWARDS MARINE SOURCES AS ALTERNATIVE NOURISHMENT SUPPLIES TO SUPPORT FOOD SOVEREIGNTY - Mufarrijul Ikhwan; Rina Yulianti (UNEJ e-Proceeding, 2017)
The overflow of marine sources of Indonesia can be alternative nourishment supplies to support food sovereignty which is currently rice oriented. One of efforts in fishery sectorutilities as the main support to food sovereignty is through coastal management. In line withthe purposes of the declaration sustainable development Goals / SDGs proposed by theUnited Nations related to food sovereignty is to conserve and sustainably use the oceans, seasand marine resources for sustainable development. In his inauguration speech, PresidentJokowi stated that maritime development will be one of the priorities of his cabinet. Since2014-2016, FAO reported the second ranked position of Indonesia as the country of fishproducers under China; Indonesia's seas achieve at least 529 of potential biota to supportfood security. This evidences that Indonesia can reach the target of food sovereignty infisheries sector. The overall sea use agrees with regulations, first, Law No. 31 Year 2004 onFisheries as amended by Law No. 45 Year 2009 on Amendment to Law No. 31 Year 2004 onFisheries, second, Law No. 27 year 2007 on The Coastal Areas and Small Islands Managementas amended by Law No. 1 Year 2014 on Amendment to Law No. 27 year 2007 on The CoastalAreas and Small Islands Management. The marine sources to support food sovereignty arerich and potential but are not supported with the government policy as shown by the pass ofcoastal reclamation application regulation. Reclamation will decrease the sources quality ofthe coastal and marine environment. Reclamation impacts the fisherman food needed fromfisheries sector because they lost ocean space and sources. Ocean grabbing by coastalreclamation threats the fisheries livelihood and damage food sovereignty from fisheriessector.